DEVELOPMENT OF PUBLIC (MUNICIPAL) MANAGEMENT OF THE SPHERE OF HOUSING AND COMMUNAL SERVICES: PROBLEMS AND PROSPECTS - G. G. Kuznetsova; A. M. Pronina (Модернизация, инновация, развитие, 2016)
The state, municipality, population and entrepreneurship interrelation mechanism is far from being perfect in Russian housing and communal services industry. The problem may be solved provided interests of all the above participants of the industry are balanced. Most reasonable is to provide for parallel functioning of the market and governmental and municipal bodies, all of them acting in accordance with respective legal norms. More power should be given to municipalities who are non-governmental local public self-management bodies formed to provide for proper living conditions topopulation within certain territory by asserting priority interests common for this population. Negative consequences of the monopoly status of suppliers and providers of communal services should be eradicated. Transition from the monopolistic and closed communal services market to that open and competitive should become general strategy of Russian housing and communal services industry development.